KINERJA KEUANGAN SEBAGAI PEMEDIASI PENGARUH INTENSITAS RESEARCH AND DEVELOPMENT DAN ASET TIDAK BERWUJUD PADA NILAI PERUSAHAAN - Kurniawan, A Prawira; Mertha, I Made (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
The purpose of this study is to understand the influence of R&D and intangible assets to a firm’s value with return on assets as a mediation variable. This study is conducted in a manufacture companies listed in Indonesian stock exchange from 2012 to 2014. Method of sample selection that used in this study is purposive sampling with four criteria. Decent samples to be observed are 30 companies. Analysis method used in this study is path analysis. The result of this study show that (1) R&D intensity and INTAV affect firm’s value, (2) R&D intensity and INTAV affect financial performance, (3) Financial affect firm’s value, (4) Financial performance fail to mediate the influence between R&D intensity and intangible assets on firm’s value.
Keywords: financial performance; research and development intensity; intangible assets; firm’s value